PENGARUH KEPEMIMPINAN DIGITAL DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KETERIKATAN KERJA SEBAGAI VARIABEL MEDIASI - Imam Arifin; Osly Usman (JURNAL LENTERA BISNIS, 2026)
This study aims to examine the effect of digital leadership and perceived organizational support on job performance, with work engagement as a mediating variable. The main issue addressed in this study is the need for public, state-owned, and private organizations to improve employee performance in an increasingly digital work environment. This research used a quantitative approach with an explanatory design. Data were collected through a closed-ended questionnaire using a Likert scale and involved 168 respondents. The data were analyzed using PLS-SEM with SmartPLS software. The results show that digital leadership has a positive and significant effect on work engagement and job performance. Perceived organizational support has a positive and significant effect on work engagement, but it does not have a significant direct effect on job performance. Work engagement has a positive and significant effect on job performance. The findings also show that work engagement partially mediates the effect of digital leadership on job performance and fully mediates the effect of perceived organizational support on job performance. The R-square values indicate that the model explains 53.7% of the variance in work engagement and 64.2% of the variance in job performance. These findings suggest that improving employee performance requires not only digital leadership and organizational support, but also stronger work engagement. Practically, organizations need to strengthen digital leadership capabilities, improve organizational support, and create a work environment that encourages employee energy, dedication, and focus.